Implementasi Maqasid Al-Shari’ah Dalam Manajemen Strategis Syariah - Mohamad Toha; Khoirur Rozikin (Universitas Islam Lamongan, 2020)
The problem faced by developing countries is the welfare of its citizens. Welfare is an important part of a country. Even the purpose of establishing a country is nothing but the welfare of its people. Various ways, rules, methods, tools, approaches and policies have been tried and carried out by the state in order to achieve these welfare goals. Not only are people in a country that wants to prosper, many companies in developing countries want welfare in the companies they manage. But these companies tend to use conventional strategic management concepts in this modern era. In fact, these companies still experience various problems, both internal and external problems. They incur huge costs to implement various modern management models, but some are lacking and do not bring satisfaction. The implementation of maqa>sid al-shari>’ah as the making of Islamic law in strategic management is very rarely used, both in terms of economy and government, people are more likely to use conventional strategic management concepts proposed by scientists from the west. This is what causes fraud or dishonesty in managing a company. Therefore this paper is intended to examine the implementation as a form of Islamic law in sharia strategic management. This paper explains that the concept of conventional strategic management is considered a failure in regulating one's behavior towards a better organization. The implementation of maqa>sid al-shari>’ah as making Islamic law in sharia strategic management is considered by the author as a better alternative than conventional strategic management concepts. Keywords: maqa>sid al-shari>’ah, islamic law, sharia strategic management